Pelaksanaan Gotong Royong Untuk Meningkatkan Kesadaran Masyarakat Dalam Kebersihan Lingkungan - Apriani, Denny; Pratama, Yoga Anugra; Amelia, Amelia; Ardiansyah, Rivaldo Dwi; Pratama, Yolan Agung; Wijaya, Ermy; Yulianti, Liza; Irwanto, Tito (Jurnal Gotong Royong, 2025)
This research investigates the implementation of a waste segregation system focusing on organic and inorganic waste to improve environmental awareness within the Pematang Gubernur community in Bengkulu. The study employed a participatory approach, which involved community engagement through seminars, workshops, and direct outreach to households. The primary aim was to educate the residents on the importance of waste segregation and provide the necessary facilities to support sustainable waste management practices. The results indicate that the training successfully raised awareness and encouraged the community to adopt better waste management habits. Moreover, the program fostered a sense of responsibility among the residents, contributing to improved community collaboration in maintaining a clean and sustainable environment. The study concludes that such community-driven initiatives are essential for fostering long-term environmental sustainability.